The effects of selected soil physical properties on the soil water balance, soil water redistribution and pyrrolizidine alkaloids loads in two diferent textured soils in the nieuwoudtville rooibos tea production area - Olifant, Kagisho Ignitious (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.